Analisis Kepatuhan Kerja Anggota di Polsek Pademangan - Natasia Tri Utami; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2024)
This research discusses the work of the members of the Pademangan Police Substation (Polsek Pademangan). It utilizes a qualitative research approach with the aim of understanding the compliance of the members at Polsek Pademangan. Compliance is an attitude or behavior of individuals or groups that adhere to rules, norms, or regulations established by the relevant authorities or organizations. Compliance can also be defined as the attitude or behavior of individuals or groups in following and adhering to established rules, norms, or regulations. Compliance reflects an individual's adherence to prevailing standards, whether they be legal, organizational rules, ethics, social norms, or other provisions governing behavior and actions. The purpose of compliance is to maintain order, justice, security, and efficiency in various life contexts, such as within society, organizations, or government institutions. Through compliance, an individual or group is expected to behave in accordance with established norms and not violate existing rules. Compliance often serves as the foundation for the functioning of law, ethics, and management in various sectors of life, including the business world, education, government, and society. Compliance can also be linked to an individual's responsibility towards their environment and the surrounding community. Through compliance, individuals contribute to the development and maintenance of norms that help preserve harmony and the common good. In various aspects of life, compliance is an important principle for maintaining social function and running organizations or communities efficiently and fairly.